SOLUTION: 10^(2x-1)=e^(4x-3)

Algebra ->  Algebra  -> Logarithm Solvers, Trainers and Word Problems -> SOLUTION: 10^(2x-1)=e^(4x-3)      Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Logarithm Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on logarithm Question 49306: 10^(2x-1)=e^(4x-3)Found 2 solutions by Nate, atif.muhammad:Answer by Nate(3500)   (Show Source): You can put this solution on YOUR website!10^(2x - 1) = e^(4x - 3) ln(10^(2x - 1)) = ln(e^(4x - 3)) (2x - 1)ln(10) = 4x - 3 2x*ln(10) - ln(10) = 4x - 3 2x*ln(10) - 4x = ln(10) - 3 x(2*ln(10) - 4) = ln(10) - 3 x = (ln(10) - 3)/(2*ln(10) - 4) About -1.1524 Answer by atif.muhammad(135)   (Show Source): You can put this solution on YOUR website!```10^(2x-1)=e^(4x-3) Apply ln function to both sides ln 10^(2x-1)=ln e^(4x-3) ln 10^(2x-1)=(4x-3) --- After cancelling the ln and e on the right hand side. (2x-1) ln 10 = (4x-3) 2xln 10 - ln 10 = 4x-3 2xln 10 - 4x = ln 10 - 3 x(2ln10 -4) = ln 10 -3 x = ```